Study of Î²-Catenin as Immunohistochemistry Marker in Women with Breast Cancer - Salman, Ruqayah Ali; AlBairuty, Genan Adnan Abdullatef; Abdul-Rasheed, Omar F. (Iraqi Journal of Science, 2021)
Background & Objective: Breast cancer (BC) is the most prevalent disease among women around the world, considered the world's leading cause of death (15% of the total cancer deaths) in women in 2018. Î²-catenin is a multifunctional protein located in the cytoplasm and/or nucleus of the cell. Several studies suggested that Î²-catenin expression plays a critical role in cancer invasion and metastasis. This research sought to examine Î²-catenin expression in breast cancer and its associations with clinico-pathological features (such as histopathological types, grade, and invasion depth of tumor as well as lymph node involvement) and breast cancer patient survival. Methods: The study was performed in the period from 1 January to July 2019 on 40 female breast cancer patients. The control group involved 40 healthy females with no history of cancer. Tissue blocks from histologically confirmed patient and control subjects were fixed in formalin and embedded in paraffin . Î²-catenin was evaluated by immunohistochemistry (IHC). Results: The immunohistochemical study of the subcellular localization of Î²-catenin demonstrated that 75% of the patients showed 1-3 score for Î²- catenin compared to only 27.5% of controls who had such score, with a highly significant difference. Conclusions: The use of Î²-catenin IHC markers can be effective throughout the treatment of progressive BC.